Upaya Mempertahankan Ekonomi Keluarga dan Kesehatan Ibu Di masa Pandemi kepada Para Difabel - Ferida Rahmawati; Emi Nurlaela; Laila Zulfa; Anindita Mutiara Tantri (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
People with disabilities during the COVID-19 pandemic have experienced economic changes in their families. Changes in the family economy have an impact on changing almost all life activities, including improving maternal health. This community service aims to increase the knowledge of people with disabilities in maintaining the family economy and maternal health during the pandemic. This community service activity is a planned activity. The method of activity with lectures and questions and answers. The activity took place in the Wonotunggal area, Batang Regency. The activity was conducive. There are 33% of active audience asking. The audience expects skills training and permanent jobs that can be carried out by disabled groups in government and private offices. 75% of the audience really feel the economic changes. The results of this activity included a change in the number of audiences who behaved well in dealing with the pandemic from 33% before counseling to 47% after counseling. 47% of the audience is very confident that they can meet their nutritional needs despite economic changes during the COVID-19 pandemic and limitations due to their disabilities. Independent attitude is felt in 40% of the audience. This change in attitude towards the family's economic condition during the COVID-19 pandemic and theattitude of maintaining their health. Suggestion: to increase the quantity and quality of community service in maintaining and improving the family economy and maternal health in the disabledgroup with differentmethods such as skills training so as to increase motivation, increase self-confidence in the community.